2020
DOI: 10.1016/j.ijscr.2020.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of a double myelomeningocele in the upper thoracic and thoracolumbar spine: A case report

Abstract: Highlights Multiple neural tube defects is very uncommon. High morbidity in multiple neural tube defects compared to single defects. Association of other spinal cord and vertebral malformation with multiple neural tube defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the same context, our patient was free of any associated congenital anomalies. Elarjani et al [25] reported the association of hydrocephalus and scoliosis with double upper thoracic and thoracolumbar MMC; in addition, 29.8% of NTD The patient in this case was operated at 2 months of age. However, it is recommended to perform surgery as soon as possible, particularly in patients diagnosed prenatally, the optimal time for surgery of MMC cases is known to be within the first 5 days as per Oncel et al [27].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In the same context, our patient was free of any associated congenital anomalies. Elarjani et al [25] reported the association of hydrocephalus and scoliosis with double upper thoracic and thoracolumbar MMC; in addition, 29.8% of NTD The patient in this case was operated at 2 months of age. However, it is recommended to perform surgery as soon as possible, particularly in patients diagnosed prenatally, the optimal time for surgery of MMC cases is known to be within the first 5 days as per Oncel et al [27].…”
Section: Discussionmentioning
confidence: 65%
“…In the same context, our patient was free of any associated congenital anomalies. Elarjani et al [25] reported the association of hydrocephalus and scoliosis with double upper thoracic and thoracolumbar MMC; in addition, 29.8% of NTD cases were associated with hydrocephalus in Algeria as Rintoul et al [26].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the number of centers offering this fetal intervention for selected cases with isolated OSB is growing worldwide [6,7]. Double neural tube defects on the spine are rare, accounting for less than 1% of all defects [8], and are considered a severe condition associated with hydrocephalus often requiring postnatal ventriculoperitoneal shunting, severe motor and neurological impairment, and even infant death [9][10][11][12][13][14][15]. There are only a few cases of double neural tube defects reported in the literature, with a very small proportion of them having been diagnosed prenatally [15,16], and all of them receiving postnatal surgical repair [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the number of centers offering this fetal intervention for selected cases with isolated OSB is growing worldwide [6, 7]. Double neural tube defects on the spine are rare, accounting for less than 1% of all defects [8], and are considered a severe condition associated with hydrocephalus often requiring postnatal ventriculoperitoneal shunting, severe motor and neurological impairment, and even infant death [9‒15]. There are only a few cases of double neural tube defects reported in the literature, with a very small proportion of them having been diagnosed prenatally [15, 16], and all of them receiving postnatal surgical repair [17‒19].…”
Section: Discussionmentioning
confidence: 99%